2017
DOI: 10.1111/ijag.12285
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐doped 58S bioactive glass as an anti‐Leishmania agent

Abstract: Bioactive glasses (BG) incorporating antimicrobial agents can be effectively used against microorganisms. In this work, the in vitro effectiveness of silver-doped 58S BG (BGAg) against Leishmania species was studied. BG, BGAg1, and BGAg2 belonging to the system 58SiO 2 •(36-x) CaOÁ6P 2 O 5 ÁxAg 2 O, where x=0, 1, and 2 mol.% Ag, were synthesized via sol-gel, and characterized by scanning electron (SEM) and atomic force (AFM) microscopy, thermogravimetric analyses (TGA), X-ray diffraction (XRD), Fourier-transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Up to now, most of these studies have been conducted on the skin and nerve tissues with satisfactory results [ 102 , 103 , 104 , 105 ]. Furthermore, the use of melt-derived and sol-gel BGs in the repair and regeneration of cardiac and lung tissues has also been reported with early promising results [ 73 , 74 , 75 , 76 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. In this pioneering set of studies, BGs have been usually incorporated in polymeric matrices that match better the physico-mechanical properties of soft and delicate cardiac/lung tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, most of these studies have been conducted on the skin and nerve tissues with satisfactory results [ 102 , 103 , 104 , 105 ]. Furthermore, the use of melt-derived and sol-gel BGs in the repair and regeneration of cardiac and lung tissues has also been reported with early promising results [ 73 , 74 , 75 , 76 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. In this pioneering set of studies, BGs have been usually incorporated in polymeric matrices that match better the physico-mechanical properties of soft and delicate cardiac/lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that doping of 58S sol-gel glass with moderate amounts of silver (2 mol % Ag 2 O max.) to obtain an antibacterial BG elicited no toxic effects towards A549 cells in vitro [ 87 ].…”
Section: Applications In Lung Tissue Engineeringmentioning
confidence: 99%
“…Ions such as silver and gallium have demonstrated antibacterial properties [19,20], whereas cobalt can stimulate new blood vessel formation [21,22], similar effect observed in copper-doped glasses [23]. Those ions can be released during the glass dissolution process, improving the glass biological effect.…”
Section: Introductionmentioning
confidence: 96%
“…Other samples presented cell viability rates of about 70%, with no significant difference between these values. The test depicted in Figure 7 suggests that the material was highly biocompatible 33 , but the mechanism of cell/fiber interaction will be examined in future studies. Figure 8 depicts the in vitro bioactivity of fibers immersed in SBF solution for 7 days and 14 days.…”
mentioning
confidence: 99%
“…Due to its nanofibrous structure, the surface of the fibers allows biomimicry to accommodate and induce the formation of apatite. These nanofibers act as nuclei for the crystallization process 33 . This is confirmed by high surface area nanometric and submicrometric fibers used in place of commonly agglomerated powders 12,[35][36][37][38] .…”
mentioning
confidence: 99%